An Examination of the Westermarck Hypothesis and the Role of Disgust in Incest Avoidance Among Fathers. (23rd May 2019) - Pullman, Lesleigh E.; Babchishin, Kelly; Seto, Michael C.
From an evolutionary perspective, incestuous behavior is puzzling. The goal of this study was to assess the tenability of the Westermarck hypothesis (1891, 1921)—that people who live in close physical proximity with one another during childhood will develop a sexual indifference or aversion toward one another—and the mediating role of disgust as an incest avoidance mechanism in father–daughter relationships. A sample of fathers with daughters ( N = 632) from Canada and the United States were recruited by Qualtrics—a survey platform and project management company—to complete an online survey. The results from this study did not support the viability of the Westermarck hypothesis as a mechanism that facilitates incest avoidance for fathers. Physical proximity was not associated with incest propensity or disgust toward incest. Less disgust toward incest, however, was found to be associated with more incest propensity. These results indicate that physical proximity may not be a reliable kinship cue used by fathers to inform incest avoidance, but that disgust toward incest may still be a proximate mechanism that facilitates incest avoidance among fathers using kinship cues other than physical proximity.